Edukasi Tentang Faktor Risiko, Serta Bahaya Obesitas pada Pandemi Covid 19 di Poli Penyakit Dalam Rumah Sakit Akademik Universitas Mataram - Catarina Budyono; Anak Agung Sagung Mas Meiswaryasti P; Ima Arum Lestarini; Novia Andansari Putri R; Niti Wedayani; Eka Arie Yuliani; Sekar Partiwi (Universitas Mataram, 2022)
The impact of obesity is quite wide on various chronic degenerative diseases such as hypertension, coronary heart disease, stroke, cancer and type 2 diabetes and bone disorders. Due to the many diseases that can be caused by obesity, the morbidity and mortality rates of obese people are quite high. So that obesity has an impact on health costs both directly and indirectly. The prolonged pandemic causes people to be lazy to do sports and tend to work from home. Not regulating healthy eating and living patterns, which can lead to Obesity Nutritional status which can affect various diseases, so it is necessary to educate about the risk factors and dangers of obesity during the COVID-19 pandemic. The approach steps taken in this program are counseling or providing education to visitors to the Internal Medicine Poly at Mataram University Hospital. Community service is carried out at the UNRAM Hospital Poly and also in the UNRAM Hospital hall. Attended by 35 participants and 1 speaker as well as 4 young doctors and 1 lab employee from the Faculty of Medicine, University of Mataram who distributed questionnaires and flyers about obesity. From the analysis of the questionnaire distributed, 32 people scored less than 50 in answering questions about risk factors and the dangers of obesity and there was a change in the score to 29 respondents who scored 80 after being given education. From these results, it is important to conduct regular education to reduce the severity and prevent the occurrence of metabolic syndrome due to obesity.